2017
DOI: 10.1093/ntr/ntx030
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Implementing the All Nations Breath of Life Culturally Tailored Smoking Cessation Program for American Indians in Multi-Tribal Urban Communities

Abstract: This is the first large feasibility study of a culturally tailored smoking cessation program for American Indians with good cessation and retention rates in a multi-tribal urban American Indian population. It shows that All Nations Breath of Life can be implemented in multiple urban settings across five states. To our knowledge, this is the first program of its kind to be implemented across multiple heterogeneous urban locations and to include salivary cotinine testing for verification of self-report data acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…While there is clear support in the literature for addressing sacred uses of tobacco in intervention materials targeted towards AI/AN communities, [2931, 35] the focus groups in our formative research found this to be contentious, with mixed opinions on whether or not it was appropriate to include in educational materials. While the ultimate consensus was that traditional uses of tobacco should not be neglected, concerns were iterated that traditional tobacco should not be associated with concerns about SHS in the home or commercial smoking, or did not need to be addressed given sufficient knowledge in communities.…”
Section: Discussionmentioning
confidence: 80%
“…While there is clear support in the literature for addressing sacred uses of tobacco in intervention materials targeted towards AI/AN communities, [2931, 35] the focus groups in our formative research found this to be contentious, with mixed opinions on whether or not it was appropriate to include in educational materials. While the ultimate consensus was that traditional uses of tobacco should not be neglected, concerns were iterated that traditional tobacco should not be associated with concerns about SHS in the home or commercial smoking, or did not need to be addressed given sufficient knowledge in communities.…”
Section: Discussionmentioning
confidence: 80%
“…Sixty percent of the studies reported Reach [ n = 12; ( 33 , 35–38 , 40 , 42 , 45–48 , 50 )] with information mainly focused on inclusion and exclusion criteria for participants along with recruitment strategies ( 33 , 35 , 36 , 40 , 42 , 45 , 46 , 48 , 50 ). For example, Campbell and colleagues ( 35 ) noted that they recruited 58.8% ( N = 40) out of the 68 clients that were eligible to participate in their study.…”
Section: Resultsmentioning
confidence: 99%
“…Trust was also emphasized in a few studies as another reason Reach was successful ( 36 , 37 ). A trusting relationship between the participants and the research team was key.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations